PACKAGE OF BIRTHING BALL, PELVIC ROCKING, AND ENDORPHIN MASSAGE (BPE) DECREASE THE FIRST STEP LABOR PAIN - Nila Marwiyah; Lenny Stia Pusporini (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2017)
Background and Purpose: Labor pain is unpleasant and frightening experience for birth mother. In addition, labor pain cause exhaustion and childbirth trauma.Birthing ball, pelvic rocking, and endorphin (B.P.E) massage are emerging as non-pharmacology methods of pain management in labor. The aimed of this study was to investigate the effect of package of BPE on labour pain during the first stage of labor. Method: This study was quasi-experiment. Total numbers of samples were 23 mothers who were in the first stage of labor. Samples were selected by using quota sampling technique. Instrument of this study was numeric rating scale (NRS). Result: Data analysis by using paired sample t-test revealed that there were significantly different between before and after the intervention of BPE on labour pain during the first stage of labor in this study (p <0.01).  Conclusion and recommendation: This study showed that BPE is effective as non-pharmacology methods on pain relieve of first stage of labor. Further study need to investigate other variables such as anxiety of birth mother. Key Words: labor pain, package of birth ball, pelvic rocking, and endorphin massage(BPE), labor process.